2019
DOI: 10.3390/ijms20133316
|View full text |Cite
|
Sign up to set email alerts
|

Phenformin as an Anticancer Agent: Challenges and Prospects

Abstract: Currently, there is increasing evidence linking diabetes mellitus (especially type 2 diabetes mellitus) with carcinogenesis through various biological processes, such as fat-induced chronic inflammation, hyperglycemia, hyperinsulinemia, and angiogenesis. Chemotherapeutic agents are used in the treatment of cancer, but in most cases, patients develop resistance. Phenformin, an oral biguanide drug used to treat type 2 diabetes mellitus, was removed from the market due to a high risk of fatal lactic acidosis. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Remarkably, when combined with 2-DG, or dichloroacetate the lactic acidosis incidence was reduced [169]. While there are several proposed mechanisms of action, the main mechanism of action of biguanides is inhibiting complex I of the mitochondrial respiratory chain which causes an increase in the AMP/ATP ratio, hence activating AMPK [149,170,171]. In turn, AMPK is an invaluable energy sensor for cells that is activated in conditions of low ATP.…”
Section: Biguandes (Metformin and Phenformin)mentioning
confidence: 99%
“…Remarkably, when combined with 2-DG, or dichloroacetate the lactic acidosis incidence was reduced [169]. While there are several proposed mechanisms of action, the main mechanism of action of biguanides is inhibiting complex I of the mitochondrial respiratory chain which causes an increase in the AMP/ATP ratio, hence activating AMPK [149,170,171]. In turn, AMPK is an invaluable energy sensor for cells that is activated in conditions of low ATP.…”
Section: Biguandes (Metformin and Phenformin)mentioning
confidence: 99%
“…For instance, several studies have revealed that orlistat, as an antitumor drug, inhibits tumor growth in a variety of cancers, including prostate cancer, by inhibiting fatty acid synthase [ 37 ]. Biguanides (metformin and metformin) increase the AMP/ATP ratio mainly by inhibiting mitochondrial respiratory chain complex I, thus activating AMPK, further inducing catabolism process, increasing ATP level, reducing protein and lipid synthesis, and ultimately inhibiting tumor growth [ 38 , 39 ]. This would provide new insights into metabolic therapy as an alternative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…While aerobic glycolysis is a known feature of cancer cells, targeting this pathway for therapy has proven challenging due to the cytotoxicity of many anti-glycolytic agents [25]. Biguanides, such as metformin and phenformin, are common therapeutics for the treatment of type 2 diabetes, and have recently been reported to exhibit anticancer activity in vitro and in vivo [26][27][28]. Specifically, both agents have an inhibitory effect on glycolysis and oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%